Hamletkrisen: Kleist, Shakespeare, and Media Theory circa 1800. Issue 1 (2nd January 2017) - Weigel, Moira
Abstract : This essay draws on media archaeology and the history of translation in order to challenge two arguments that have long shaped interpretations of Heinrich von Kleist and German Romanticism: (1) that Kleist wrote in reaction to Kant and (2) that Shakespeare's plays provided a model of "naturalness" to poets of the  Goethezeit . By placing Kleist's letters in conversation with the material history of the optical media to which they frequently allude, I suggest that his "crisis" centers on how media mediate perception and representation. Moreover, I propose that Kleist's performance of crisis takes its cues from  Hamlet . After closely reading several essays where Kleist invokes Shakespeare in order to argue for a "middling" aesthetic, I return to Christoph Martin Wieland's and A. W. Schlegel's translations of  Hamlet to demonstrate that the play hailed as a "mirror held up to nature" in fact constantly foregrounds the non-transparency or mediated quality of perception and communication. Finally, by examining Kant's  Dreams of a Spirit Seer (1766), I show how Kleist's "hamletisch" concerns haunt the discourse of German Idealism from within. My broader ambition is to demonstrate how "untimely" reading across languages and media might break open the "discourse networks" and historical periods that continue to structure studies of literature, even in the work of scholars who claim to depart from old orders of knowledge.